The effects of a displayed cognitive aid on non‐technical skills in a simulated 'can't intubate, can't oxygenate' crisis. (July 2014) - Marshall, S. D.; Mehra, R.
Summary Guidelines outlining recommended actions are difficult to implement in the stressful, time‐pressured situation of an airway emergency. Cognitive aids such as posters and algorithms improve performance during some anaesthetic emergencies; however, their effects on team behaviours have not been determined. In this study, 64 participants were randomly assigned into control (no cognitive aid) and intervention (cognitive aid provided) groups before a simulated 'can't intubate, can't oxygenate' scenario. Video analysis was undertaken of the non‐technical skills and technical performance during the scenarios. All categories had higher Anaesthetists' Non‐Technical Skills (ANTS) scores when a cognitive aid was supplied (mean (SD) total ANTS score 10.4 (3.1) vs 13.2 (2.4), p < 0.001). The number of times the cognitive aid was used was associated with higher ANTS scores (ρ = 0.383, p = 0.002). A trend towards the establishment of an infraglottic airway within 3 min was also noted (control group 55.3% vs intervention 76.9%, p = 0.076). Non‐technical skills are improved when a cognitive aid is present during airway emergencies.